Briquetes de resíduos urbanos: uma alternativa energética para o semiárido brasileiro. - Magalhães, Arthur Santos (Universidade Federal Rural do Semi-Árido, 2018)
In the Brazilian semi-arid region, threats to native vegetation are a problem and natural regeneration is slow in caatinga areas. This is not enough, however, to prevent the advance of vegetation suppression caused by the increase in local energy demand. This work aimed at finding an alternative to the massive exploitation of renewable resources, while proposing to produce briquettes from three types of solid waste for energy production purposes. Maçaranduba wood (Manilkara sp), residues from the construction industry, wastes from wood charcoal production and three types of paper were used to constitute nine types of briquettes. The characterization of the briquettes took place in the Laboratory of Wood Technology at the Federal Rural University of the Semi-Arid Region. The physical and mechanical properties, immediate chemistry, combustion index and heating value were analyzed for the briquettes characterization. In general, the nine types of briquettes have shown potential as energy generators. Briquettes produced with wood charcoal fines, regardless of the type of cellulosic binder used, tended to have good averages of heating value and combustion indexes. The use of a mixture of wood charcoal and wood residues resulted in briquettes of higher heating value.
Keywords: Madeira; Briquetes; Energia; Wood; Briquettes; Energy; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL